Quid du port romain estuarien de Barzan (Charente-Maritime) ? - Vivien Mathé; Laurence Tranoy; Marion Druez; François Lévêque; Vincent Miailhe; Frédéric Pouget (Gallia)
The antique town of Barzan is located on the southwestern margins of the civitas Santonum, near the right bank of the Gironde estuary. The banks of the estuary were deeply eroded during the last glaciation and formed valleys that were subsequently flooded during the Holocene transgression. Later, the progressive inflow of fluvio-marine sediments became increasingly important in filling up the valleys that had become marshes. Thus, the current landscape is the result of transformations covering the ancient shore. This knowledge is necessary to know to identify the areas suitable for port developments. Because of the location of the site and already known remains, including remains of warehouses, it has long been assumed that this was a major harbour facility. However, none of the excavations carried out previously made it possible to confirm this hypothesis. In an initial stage various geophysical survey methods were used to study an area encompassing several hectares. The methods adopted aimed to identify the extension of the marsh in order to locate the ancient shore on a wide mesh map, using two electrical resistivity tomographies (ERT) perpendicular to the supposed palaeo-shoreline. The use of a dynamic penetrometer completed this initial stage. These methods have revealed a 3-ha-wide basin, very open to the estuary to the west and penetrating and narrowing inland to the east. In a second stage, favourable areas were selected to conduct high-spatial-resolution remote sensing to identify buildings and constructions upstream from the shore. Several anomalies were thus detected on the opposite edges of the basin. One of these, exhibiting a longitudinal shape, could correspond to a quay. Two large compartmented constructions, rectangular in shape (85 to 100 m long; 15 to 25 m wide) and subdivided, are located on the opposite edges of the basin and follow the same orientation. Finally, two smaller anomalies correspond to stone constructions the foundations of which are located at a depth of approximately 2 m. They reveal structures which must therefore have been very high. It is tempting to propose to interpret these as landmarks for navigation, for example a lighthouse and/or seamark. The results obtained from the geophysical survey reveal imposing remains, of various natures, which could correspond to one of the major harbour systems of the civitas Santonum. In addition, this sector is likely to provide palaeo-environmental information whose importance goes beyond the Barzan site.